PENGARUH PENDIDIKAN TERHADAP ESENSI PEMBANGUNAN EKONOMI (Survei pada Sekolah Menengah Pertama Negeri di Kota Depok) - ALIE SADIKIN; RINOVIAN RAIS (Institut Bisnis Muhammadiyah Bekasi, 2021)
The quality of education can be realized if the combination of talent, character, ability and conscience as a whole is part of a breakthrough, the results of education will create creative and innovative products. In line with the socialization of the 2013 curriculum, students are directed to create a science and become relevant to be implemented in the real world. The results that become applied can be used as the best policy for the community.